ANALISIS STRATEGI DALAM PENGIMPLEMENTASIAN ECOTOURISM DI DESA WISATA HIJAU BILEBANTE, LOMBOK TENGAH, NTB, DI TENGAH ERA PEMBANGUNAN BERKELANJUTAN - Lalu Puttrawandi Karjaya; Rizky Akbar Danuarta; Nona Namira Najwa; Silvia Dwi Hartina; Vidrian Azandra Xeriscky (LPSDI Bina Patria, 2024)
This journal discusses ecotourism applied in Bilebante village as a form of tourism that emphasizes nature conservation and environmental sustainability. This journal aims to analyze strategies in implementing ecotourism in the green tourism village of Bilebante, Central Lombok, NTB. The method that will be used in writing this journal is qualitative research by collecting secondary data and observation through the interview process. In this context, Bilebante Village in Central Lombok, NTB, applies the concept of ecotourism to green tourism as a sustainable development effort. This itself will certainly have a domino effect on several dimensions in the economic space with a wider range, the development of ecotourism makes the local community have many options in using the benefits of tourism as employment. This research will use the concepts of ecotourism and sustainable tourism to analyze the implementation in Bilebante Village, with a focus on nature conservation, community participation, and the environment. In the end, this research is expected to conclude on how the strategy of implementing ecotourism in Bilebante Village without feeling that sustainable development is a threat to the concept of tourism applied in the village, and can provide insight to readers related to ecotourism, especially in the green tourism village of Bilebante, Lombok, NTB.